2015
DOI: 10.1103/physrevb.91.155306
|View full text |Cite
|
Sign up to set email alerts
|

Kondo effect and the fate of bistability in molecular quantum dots with strong electron-phonon coupling

Abstract: We investigate the properties of the molecular quantum dot (Holstein-Anderson) model using numerical and analytical techniques. Path integral Monte Carlo simulations for the cumulants of the distribution function of the phonon coordinate reveal that at intermediate temperatures the effective potential for the oscillator exhibits two minima rather than a single one, which can be understood as a signature of a bistability effect. A straightforward adiabatic approximation turns out to adequately describe the prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In recent years there have been a long debate about the existence of bi-stability in QDs, mostly in the presence of electron-phonon interaction. Several numerical approaches [3,4,5,6,7,8,9] and experimental results [10,11,12] confirm the appearance of this phenomenon in different QD systems, while there exist some arguments against bi-stability in some special cases [13,14,7].…”
Section: Introductionmentioning
confidence: 54%
“…In recent years there have been a long debate about the existence of bi-stability in QDs, mostly in the presence of electron-phonon interaction. Several numerical approaches [3,4,5,6,7,8,9] and experimental results [10,11,12] confirm the appearance of this phenomenon in different QD systems, while there exist some arguments against bi-stability in some special cases [13,14,7].…”
Section: Introductionmentioning
confidence: 54%
“…For instance, it has been shown that the displacement fluctuation spectrum of a nanomechanical oscillator strongly coupled to electronic transport, either in the regime of semiclassical phonons [101,102], or for a quantum nanomechanical oscillator entering the Franck-Condon regime [103] bears clear signatures of a transition to a bistable regime. Moreover, by making a mapping to the Kondo problem, the bistability was shown to be destroyed in equilibrium conditions by quantum fluctuations if the temperature is lower than a phonon mediated Kondo temperature [53]. Notice, however, that this phonon displacement bistability does not correspond necessarily to a bistable behavior for the charge or the current, as predicted by the mean field approximation.…”
Section: Hartree Solutionmentioning
confidence: 98%
“…The most interesting and general coherentinteracting regime constitutes a great theoretical challenge. This regime has been addressed using several complementary approaches: diagrammatic techniques [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], quantum Monte-Carlo (MC) [48][49][50][51][52][53][54][55], timedependent NRG [56][57][58][59][60][61][62][63], time-dependent DFT [64][65][66][67][68][69][70] among others [71][72][73][74][75].However, all of these techniques as they are actually implemented have some limitations. For instance, numerically exact methods like quantum MC are strongly time-consuming, require finite temperature and typically do not allow to reach long time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an imaginary-time formulation [93][94][95] as well as a Wigner-space representation 95,96 has been proposed. Other numerically exact methods to simulate vibrationally coupled charge transport in nanosystems include iterative path integral approaches, [97][98][99] diagrammatic quantum Monte Carlo simulations, [100][101][102][103][104][105] the numerical renormalization group technique, 60,61,106,107 the multilayer multiconfiguration timedependent Hartree method. 10,[108][109][110][111][112] In this paper, a hierarchical quantum master equation (HQME) approach is formulated to study vibrationally coupled charge transport.…”
Section: Introductionmentioning
confidence: 99%